Drip-and-Ship for Thrombectomy Treatment in Patients With Acute Ischemic Stroke Leads to Inferior Clinical Outcomes in a Stroke Network Covering Vast Rural Areas Compared to Direct Admission to a Comprehensive Stroke Center - Taschner, Christian A.; Trinks, Alexandra; Bardutzky, Jürgen; Brich, Jochen; Hartmann, Ralph; Urbach, Horst; Niesen, Wolf-Dirk (Frontiers in Neurology, 2021)
Introduction: Organizing regional stroke care considering thrombolysis as well as mechanical thrombectomy remains challenging in the light of a wide range of regional population distribution. To compare outcomes of patients in a stroke network covering vast rural areas in south-western Germany who underwent mechanical thrombectomy (MTE) via direct admission to the single comprehensive stroke center (CSC; mothership [MS]) with those transferred from primary stroke centers (PSC; drip-and-ship [DS]) we undertook this analysis of consecutive stroke patients with MTE. Material and Methods: Patients who underwent MTE at the CSC between January 2013 and December 2016 were included into the analysis. The primary outcome measure was 90-days functional independence (modified Rankin Score [mRS] 0–2). Secondary outcome measures included time from stroke onset to recanalization/end-of-MTE, angiographic outcomes, and mortality rates. Results: Three hundred thirty-two consecutive patients were included (MS 222, DS 110). Median age was 74 in both arms of the study, there was no significant difference in baseline National Institutes of Health Stroke Scale scores (median MS 15 vs. 16 DS). IV thrombolysis rates differed significantly (55% MS vs. 70% DS, p=0.008). Time from stroke onset to recanalization/end-of-MTE was 112 min shorter in the MS group (median 230 vs. 342 min, p <0.001). Successful recanalization (TICI 2b-3) was achieved in 72% of patients in the MS group and 73% in the DS group in both groups. There was a significant difference in 90-days functional independence (37% MS vs. 24% DS, p=0.017), whereas no significant differences were observed for mortality rates at 90-days (MS 22%, DS 17%, p=0.306). Discussion: Our data suggests that patients who had an acute ischemic stroke admitted directly to a comprehensive stroke center may have better 90-days outcomes than those transferred secondarily for thrombectomy from a primary stroke center.